EFEKTIVITAS PERENCANAAN TENAGA KERJA PADA PT. NUTRIFOOD SURABAYA - Yuliasri, Alif Hafifah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out the role of management audit on the human resources function in appraising the employeeâs performance at PT Nutrifood Indonesia which is located on Jl. Brebek Industri VII/14 Surabaya as well as to find out problems that hold up the performance of human resources function. The human resources function at PT Nutrifood Indonesia Surabaya consists of: employeeâs planning, employeeâs recruitment, employeeâs selection, and placement, compensation and reward, as well as employment termination. The method used in this research is descriptive qualitative method, where the data collected from the field and facts which occur in company is analyzed then compared with existing theory in order to produce a good system in making decision by using data collection technique such as interview, questionnaire, documentation, and observation. Based on the research result shows that there are still weaknesses which are employeesâ planning is ineffective because there is no written document related to the employeesâ planning, employeesâ placement is inappropriate with their education background which the standard set must be minimum of D3 or S1.Keywords: Management Audit, Human Resources Function, Performance Assessment.